Alcohol consumption and viral load are synergistically associated with CIN1. - Kyung-Jin Min; Jae-Kwan Lee; Sanghoon Lee; Mi Kyung Kim (PLoS ONE, 2013)
PURPOSE: We investigated the association between alcohol consumption and risk of cervical intraepithelial neoplasia (CIN) and cervical cancer, and determined whether these associations were modified by human papillomavirus (HPV) viral load in high-risk HPV-positive women participating in the Korean HPV cohort study (KHPV). METHODS: Among the women recruited in the KHPV (n = 1,243) from March 2006 to December 2009, we analyzed normal cytology (n = 581) as control group, CIN1 (n = 299), CIN2/3 (n = 161), or cervical cancer (n = 202). Multinomial logistic analysis was performed to estimate multivariate-adjusted odds ratios (OR). RESULTS: Alcohol drinkers had an increased risk of CIN1 (OR = 2.18, 95% CI 1.22-3.89) compared with non-drinkers after adjusting for potential confounders. Subjects with more frequent alcohol consumption had a higher risk of CIN1 (p for linear trend <0.0001). Higher ethanol consumption was associated with an increased risk of CIN1 (p for linear trend = 0.0001). We also observed a synergistic effect between HPV viral load and alcohol consumption: drinkers with a high HPV viral load (≥100 RLU/PC) were associated with a significantly increased risk of CIN1 (OR = 19.1; 95% CI, 6.60-55.3, interaction p<0.001). There were no associations between alcohol drinking and CIN2/3 or cervical cancer. CONCLUSIONS: HPV viral load and alcohol was associated with the risk of CIN1 among high-risk HPV-positive women. This is the first demonstration that alcohol is an independent and combined risk factor of CIN1.